Analyzing Social Factors Influencing Religious Beliefs of Learners - Mustafa, Hishyar Sardar (International Journal of English Literature and Social Sciences (IJELS), 2019)
The purpose of this research is to examine the relationship between culture and religion on the other hand family and religion. A quantitative method used to analyses the present research. Multiple regression analysis used in this study, as seen in table (6), the coefficients analysis shows the B value for culture = .884> 0.01, which supported the first research hypothesis which stated that there is a significant and positive relationship between culture and religious beliefs of learners, the B value for family= .884> 0.01, which supported the second research hypothesis which stated that there is a significant and positive relationship between family and religious beliefs of learners. However, the findings proved that the heights value was found to be for culture factor influencing religious beliefs of learners.